2019
DOI: 10.2147/idr.s187861
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence and antimicrobial resistance of <em>Shigella</em> species isolated from diarrheal patients in Ahvaz, southwest Iran</p>

Abstract: IntroductionShigellosis is a significant global human health problem, and Shigella is in charge of almost 165 million cases of this disease annually, of whom 163 million cases are in developing countries and 1.5 million cases are in developed countries. The main aims of the current survey were to identify Shigella spp. isolated from diarrheal patients by conventional biochemical tests, determine the antimicrobial susceptibility profiles by disk diffusion method, and detect the ipaH gene using the PCR assay.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 16 publications
4
14
1
Order By: Relevance
“…Several studies were conducted to characterize bacteria associated with gastro-intestinal infection and found Shigella sp as one of the bacteria associated with diarrhea. The inding of this study was in conformity with that of Elmanama and Abdelateef [24] in Palestine and Sheikh, et al [25] in Iran who both found Shigella in stool sample of Children diagnosed with diarrhea as 16.7% and 13.2% respectively. Similar study was conducted by Obi, et al [26] on enteric bacterial pathogen in stools of residents of urban and rural regions of Nigeria, the results shows the most frequently encountered pathogens in rural area are E. coli, followed by Salmonella, Shigella, Enterobacter and Campylobacter.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies were conducted to characterize bacteria associated with gastro-intestinal infection and found Shigella sp as one of the bacteria associated with diarrhea. The inding of this study was in conformity with that of Elmanama and Abdelateef [24] in Palestine and Sheikh, et al [25] in Iran who both found Shigella in stool sample of Children diagnosed with diarrhea as 16.7% and 13.2% respectively. Similar study was conducted by Obi, et al [26] on enteric bacterial pathogen in stools of residents of urban and rural regions of Nigeria, the results shows the most frequently encountered pathogens in rural area are E. coli, followed by Salmonella, Shigella, Enterobacter and Campylobacter.…”
Section: Discussionsupporting
confidence: 91%
“…The total DNA was extracted from fresh colonies of Enterobacteriaceae isolates by the boiling method as described previously. 12 Briefly, 2 or 3 colonies of an overnight growth of each isolate on nutrient agar (Merck Co., Darmstadt, Germany) were suspended in 500 mL of DNase-and RNasefree water. The suspension was boiled at 100°C for 10 min in a dry block incubator (Polystat 5; Bioblock Scientific, France), then centrifuged at 14,000 g for 10 min.…”
Section: Dna Extractionmentioning
confidence: 99%
“…Despite higher sensitivity and speci city, this method is very expensive so many researchers have made efforts to develop new alternatives. Because of high-cost, complicated, and sensitive production process of monoclonal antibodies in serology-based methods, molecular assays as well as DNA based techniques are preferred to be developed for species identi cation of bacterial pathogens [15]. However, identi cation of S. dysenteriae because of harboring shig-toxin encoded gene as an individual marker of this pathogen is not regarded as a real challenge in comparison with identi cation of other species [16].…”
Section: Resultsmentioning
confidence: 99%
“…Biochemically con rmed colonies were further serologically analyzed for Shigella species identi cation. Serological identi cation was carried out using slide-agglutination test with DIFCO Shigella species speci c antisera (Difco Lab, Michigan, USA) as the gold standard assay [15].…”
Section: Shigella Isolation and Species Identi Cationmentioning
confidence: 99%